At the Pivot of East and West Ethnographic, Literary, and Filmic Arts - Fischer, Michael (Experimental Futures, 2023)
Michael M. J. Fischer examines documentary filmmaking, literature, and innovative dance from Southeast Asia and Singapore for their para-ethnographic insights into politics, culture, and aesthetics.